Pelatihan Penggunaan Aplikasi Alat Bantu Pengambilan Keputusan dalam KB di Klinik Permata Hati Karanganyar - Erna Wati; Aris Prastyoningsi; Wijayanti Wijayanti; Deny Eka W; Arista Apriani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
The factor for increasing the maternal mortality rate is the risk of 4 Too (too young, too close birth spacing of less than 3 years and too many more than 2 (two) children). The percentage of mothers who died giving birth under 20 years and over 35 years was 33 % of all maternal deaths, so that family planning programs can be implemented with health education, 33% of maternal deaths can be prevented through the use of contraception. Interviews were conducted at the Permata Hati clinic, several postpartum mothers did not know in detail about the types of family planning and its benefits and effectiveness. The aim is to increase mother's knowledge with training on the use of decision-making aids in family planning at the Permata Hati Clinic method with a pre post one group design. posts that experienced an increase were 24 postpartum mothers, and 1 that experienced a decrease